2019
DOI: 10.1093/jcbiol/ruz070
|View full text |Cite
|
Sign up to set email alerts
|

Nests placements and spawning in the endangered horseshoe crab Tachypleus tridentatus (Leach, 1819) (Merostomata: Xiphosurida: Limulidae) in Sabah, Malaysia

Abstract: Horseshoe crab populations are declining worldwide, and Tachypleus tridentatus (Leach, 1819) has recently been classified as Endangered in the IUCN Redlist. Among the keys for species survival is successful reproduction. Although there are reports on the reproduction, particularly details on the spawning behaviour, of the American species, Limulus polyphemus (Linnaeus, 1758), information on Southeast Asia species is very scant. This field study reports the nesting activities of T. tridentatus at Jambongan Isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…This study suggests that beach elevation is an adequate parameter for predicting the suitable spawning zone for T. tridentatus (Table 3). The estimated suitable spawning zone was highly compatible with other T. tridentatus habitats with a wide range of grain compositions – fine to medium sand in the present study, medium to coarse sand in Fukuoka (Wakamiya, 1989), gravelly sand in Imari (Botton et al, 1996) and fine to medium sand in Malaysia (Mohamad et al, 2019) – indicating that the beach elevation model can be applied to other T. tridentatus spawning grounds.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This study suggests that beach elevation is an adequate parameter for predicting the suitable spawning zone for T. tridentatus (Table 3). The estimated suitable spawning zone was highly compatible with other T. tridentatus habitats with a wide range of grain compositions – fine to medium sand in the present study, medium to coarse sand in Fukuoka (Wakamiya, 1989), gravelly sand in Imari (Botton et al, 1996) and fine to medium sand in Malaysia (Mohamad et al, 2019) – indicating that the beach elevation model can be applied to other T. tridentatus spawning grounds.…”
Section: Discussionsupporting
confidence: 81%
“…In Japan, almost all nests in the significant T. tridentatus spawning habitats in Kyushu were found within the same tidal range: 86% (378 of 439 nests) in Imazu, Kafuri, Tsuyazaki and Sone habitats of Fukuoka (Wakamiya, 1989), 97% (400 of 414 nests) in Imari, Saga (Sekiguchi, 1999). Although comparative studies are limited in other Asian countries due to the lack of T. tridentatus spawning data (Wang et al, 2020), 75% of the nests (51 in 68 nests) were detected within the same tidal range in Malaysia (Mohamad et al, 2019). Thus, it can be concluded that although the sample size in this study was small ( n = 43) due to the rapid decline of the horseshoe crabs in the area (Itaya et al, 2019; Itaya, Wada & Shuuno, 2022), the estimated suitable zone reflects the actual spawning preference of the species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some others explained that this crab has a wide dispersal abilities based on long-term studies. Individual distances up to 30 km have been observed in Malaysian crabs ( Mohamad et al, 2019 ), while the movement abilities of tri-spined horseshoe crab did not exceed 150 km ( Yang et al, 2007 ). Similarly, the American horseshoe crab in the Great Bay Estuary (USA) has a maximum mean annual linear distance ranging between 4.5 km and 9.2 km ( Schaller, Chabot & Watson, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…97% of T. tridentatus spawning was found between the EHTL and the MHWN in Imari, Japan, but most were concentrated near the mid intertidal zone (Sekiguchi, 1999). In Malaysia as well, more than 50% of T. tridentatus spawning was concentrated in the mid intertidal zone (Mohamad et al, 2019). The Atlantic horseshoe crab (Limulus polyphemus) laid their eggs between the high intertidal and the mid intertidal zones.…”
Section: Egg Survival Ratementioning
confidence: 99%